Children and adults skeletal complications of Brucellosis - MR Hassanjani Roshan (Babol University of Medical Sciences, 2003)
Background and Objective: Skeletal complications are common in brucellosis. Early diagnosis of these complications may prevent surgical procedures. The aim of this study was to evaluate the skeletal complications of brucellosis in Babol town. Methods: This study was conducted on patients with skeletal complications of brucellosis referred to infectious diseases and orthopedic departments during 1998-2001. Skeletal complications and laboratory test results were recorded in questionnaire. Proportions were compared with X² and Fisher exact tests. Findings: From 431 cases, 161 (37.6%) were with skeletal complications (94 [58.4%] were male and 67 [41.6%] were female). Mean age±SD of adults and children were 34±17.6 and 9.5±4.2 years, respectively. Among 127 adult cases, 79 (62%) had peripheral arthritis which in 48 (37.8%) cases was as monoarthritis. Peripheral arthritis was seen in 32 (94%) of 34 cases of children, which in 26 (76.5%) was as monoarthritis. Peripheral arthritis and hip involvement in children were more common than adults (P<0.05), but spondylitis was more common in adult cases (P<0.05). In 14 (8.7%) cases, brucellosis was diagnosed after surgery. Normal erythrocyte sedimentation rate (ESR) and positive rheumatoid factor were seen in 80.7% and 15.5% cases, respectively. Conclusion: Since, skeletal complications of brucellosis is similar to septic arthritis and also rheumatologic disorders and monoarthritis are the most common form of these complications therefore, it is recommended that in endemic regions, brucellosis should be considered in differential diagnosis of all cases with monoarthritis.